Cidade concentrada: compactação urbana na escala da megacidade - Oliveira, Lilian Regina Machado de (2009)
This work is about the population and geographical growth of the cities in general, in a context of exhaustion of the natural resources in our Planet. It considers some of the works of the Dutch office of architecture MVRDV, showing their work style, and displays a general view of the megacities of our time, with special attention to the city of São Paulo.